The Effect of Attribution, Brand Image, Price Perception, Social Value, and Quality Perception on Buying Decisions - Irma Tuti Handayani; Popong Nurhayati; Linda Karlina Sari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia holds strong potential in the global modest fashion market; however, local brands still face challenges due to the dominance of imported products, stronger international brand reputations, and the rapid shift toward e-commerce. This study examines consumer perceptions and determinants of purchase decisions for local modest fashion products in Indonesia. Using SEM-PLS with data from 190 female respondents aged above 18 in the Jabodetabek area who purchased modest fashion in the past six months, results show that quality perception and attribution significantly affect purchase decisions, while price perception and social value do not. Brand image, although correlated with other variables, was not statistically significant in the final model. Findings reveal that consumers are predominantly young, digitally active, and prioritize authenticity, aesthetics, and self-expression. Practically, local brands should leverage emotional and symbolic values through digital storytelling, culturally grounded branding, and value-based differentiation to strengthen competitiveness. Strategically, focusing on digital marketing, social media engagement, and authentic brand narratives can enhance consumer loyalty and sustainability in Indonesia’s modest fashion industry.